MEDICINAL PROPERTIES OF CALENDULA OFFICINALIS L. AND ITS CULTIVATION POTENTIAL IN KARAKALPAKSTAN (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Calendula officinalis L. (commonly known as pot marigold) is a widely cultivated medicinal and ornamental plant. This study investigates the biological characteristics of various Calendula cultivars, their pharmacological significance, and the feasibility of cultivating them under the climatic conditions of Karakalpakstan. The research analyzed four cultivars — Ramon, Kalta, Sozy Egypt, and Tetnik — focusing on their flowering period, growth dynamics, and the concentration of bioactive compounds.